Desenvolvimento regional da área de influência do Programa de Integraç\~ao do S\~ao Francisco - César Nunes de Castro; Monise Terra Cerezini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– To try to minimize the adverse effects of low water availability on the population and on the economy of part of the semiarid region, the Federal Government put into practice, in 2007, the S\~ao Francisco Integration Project (PISF). The PISF, known simply as the S\~ao Francisco transposition, represents an ambitious water infrastructure project aimed at increasing water supply in the most arid region of Brazil. Due to the relative socioeconomic backwardness of the region benefiting from the PISF, easily verifiable by the analysis of different indicators, the objective of contributing to the socioeconomic development of the vast territory included in the project's direct and indirect areas of influence was linked to the transposition. Evaluating public policies that promote regional development in municipalities included in PISF's influence area is the objective of this article. Most of the 398 municipalities in the PISF's area of influence are classified, according to the typology of the National Policy for Regional Development (PNDR) (Brasil, 2017), in the priority classes (low and middle income) for receiving funding from Brazilian regional policy. In general, there are several signs of the State's action in the region. On the one hand, as a positive point, there is a high coverage of social programs with repercussions on regional development, such as Bolsa Família. On the other hand, some negative points were identified, such as little attention in the region's development plans for the industrial sector, an important source of employment, and inconsistency between the operation of the Constitutional Fund for the Northeast (FNE), and the premises of the PNDR.
Keywords: R10; 330; regional development; social policy; S\~ao Francisco River Basin water transfer